Strategies for the use of cone beam tomography in teeth with suspected root fracture. Report of case series - Landa de Bellera, Rossana (2022)
Root fractures are after caries and periodontal disease, the third cause of loss of dental units, being very common in posterior and endodontically treated teeth. The symptoms they produce are ambiguous and their diagnosis depends on the combination of multiple clinical and imaging factors. Among the diagnostic studies available to establish the origin of the symptoms is the cone beam computed tomography (CBCT). The objective of this case report is to describe the strategies used in the acquisition and interpretation of the CBCT in three patients with suspected root fractures. The use of a reduced field of view, with a voxel of 0.150 mm or less, accompanied by dynamic volume exploration made it possible to detect bone defects as an indirect sign for locating root fracture lines.